Computer-linked Image Analysis of Nuclear Area: Is There a Use in Diagnosis and Grading of Hepatocellular Carcinoma? - Cheah, Phaik Leng; Looi, Lai Meng (College of Pathologists, Academy of Medicine Malaysia, 2007)
Hepatocellular carcinoma (HCC) ranks as the fifth most common cancer with an increasing frequency worldwide. “Nuclear atypia”, one of the critical features in histological diagnosis of malignancy and grading of the tumour, is generally ascertained through eyeballing. A study was conducted at the Department of Pathology, University of Malaya Medical Centre to assess whether nuclear area, (surrogate measure for nuclear size) and standard deviation (surrogate measure for nuclear pleomorphism) when objectively measured via computer-linked image analysis differs between (1) benign and malignant liver cells and (2) different grades of HCC. A 4-μm thick H&E stained section of 52 histologically re-confirmed HCC with 36 having benign, non-dysplastic surrounding liver were analysed using the Leica Q550 CW system. 10 consecutive non-overlapping, non-mitotic and non-apoptotic nuclei of HCC and surrounding benign hepatocytes respectively were manually traced at 400x magnification on the computer monitor and the nuclear area for the particular cell computed in arbitrary units by the Leica QWIN software. A total of 360 benign hepatocytic nuclei, 240 low grade HCC and 280 high grade HCC nuclei were traced. The mean nuclear area of the benign hepatocytes (37.3) was significantly smaller (p<0.05) than that of both low grade (65.2) and high grade HCC (80.0). In addition, the mean nuclear area of high grade HCC was significantly larger (p<0.05) than the low grade HCC. SD of the nuclear areas was lowest in benign hepatocytes (9.3), intermediate in low grade HCC (25.0) and highest in high grade HCC (25.6). These findings indicate that computer-linked nuclear measurement may be a useful adjunct in differentiating benign from malignant hepatocytes, in particular in small biopsies of well-differentiated tumours, and in predicting survival after surgical resection and transplant.